Enhancing elementary students’ critical thinking character through wall magazine project implementation - Aprilia, Umi Anisa (Science Center Group, 2025)
Background: Developing students’ critical thinking character has become a central priority in contemporary elementary education, particularly through literacy-based and project-oriented instructional strategies. Classroom practices that encourage active engagement, collaborative writing, and reflective evaluation are considered essential to strengthening analytical reasoning and responsible decision-making among young learners. Objective: This study aimed to examine the effectiveness of implementing a wall magazine project in enhancing elementary students’ critical thinking character compared to conventional instructional approaches. Methods: The study employed a quasi-experimental design with a pre-test and post-test control group structure. Sixty elementary students were divided into an experimental group receiving wall magazine project-based instruction and a control group receiving traditional teaching methods. Data were collected using a validated critical thinking character assessment instrument. Statistical analyses included descriptive statistics, independent samples t-test, paired samples t-test, and normalized gain (N-Gain) analysis to measure the magnitude of improvement. Results: The findings revealed that the experimental group achieved significantly higher post-test scores than the control group (p < 0.05). The experimental class demonstrated a moderate-to-high N-Gain score, indicating substantial improvement in analytical reasoning, reflective evaluation, and collaborative problem-solving. In contrast, the control group showed only moderate improvement. These results confirm that structured wall magazine project implementation effectively strengthens students’ critical thinking character. Conclusion: The wall magazine project represents an effective project-based literacy strategy for enhancing critical thinking character in elementary education. Integrating collaborative writing, structured discussion, and reflective presentation activities can foster meaningful cognitive and character development among students.